Democratic Practice and Good Governance In Nepal - Dahal, Girdhari (Journal of Political Science, 2017)
Nepal was declared Federal Democratic Republic after the mass movement of 2006, which was institutionalized by the Constitution of Nepal promulgated through Constitutional Assembly (CA) in 2015. The Constitution of Nepal is the people’s constitution. It was a dream of people to draft their constitution from CA since 1951. Nepal has a long history of democratic movements. Democratic movements in Nepal started from the period of autocratic Rana regime back in 1940s. Nepal Praja Parisad (the first political party of Nepal) had started organized democratic movement in Nepal. Thereafter many democratic movements and revolutions took place for the establishment of federal democratic republic Nepal. Democracy and good governance are closely interrelated to one another. Democracy is called the rule of law. Legitimate government, transparent rule, accountability to the people, free and fair election, independent judiciary, and fundamental rights and duties of the people are the essential elements of good governance as well as democracy. The main objective of this paper is to explore democratic movements and the concept of good governance in Nepal. The paper also tries to analyze the role of democratic movements for democracy and the relation between democracy and good governance in Nepal. Journal of Political Science. Vol. 17, 2017, Page: 18-35